An exploratory study of the links and effects of values, preferences and scenarios on resource allocation. - Chang, Ashley Wai Leng. (2013)
Our Applied Research Project examines the correlations between Hofstede's cultural values and the various preferences of allocation methods used to mete out distributive justice. Collectivism, paternalism and power-distance were the three values chosen to predict the allocation methods of equity, equality, need and seniority. A further testing was done to see if these preferences translated to actual choices made in different scenarios. We expected the dominant preference to be used in all the scenarios presented. However, the different resources used in each scenario and the alternative distribution and recovery of it complicated this direct application. Thus we ventured into another set of hypotheses that predicted the dominant allocation preference used in each scenario type.